2016
DOI: 10.1007/s10681-016-1725-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for Fusarium and Gibberella ear rot resistance in Argentinian maize germplasm

Abstract: Fusarium verticillioides and F. graminearum cause ear rots in maize (Zea mays L.) that reduce yield and contaminate the grain with mycotoxins produced by the fungi. To map QTLs for resistance to these ear rots, a F 5 mapping population, consisting of 298 recombinant inbreds obtained by randomly selfing of the cross between LP4637 (moderately resistant) and L4674 (susceptible), was genotyped with 250 single nucleotide polymorphism markers and phenotyped 2 years for disease severity after silk inoculation with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
6
26
0
Order By: Relevance
“…More recent studies reported that although most QTL for FER are minor QTL, some major QTL whose effects on FER were validated by near-isogenic lines could be managed by marker-assisted breeding [ 54 , 55 , 56 , 57 ]. In addition, as the number of mapping populations explored increased, the overlapping of QTL for FER found in different populations started to be more common [ 55 , 58 , 59 ].…”
Section: Mapping Of Qtl For Fer And/or Fumonisin Content In Bi-parmentioning
confidence: 99%
“…More recent studies reported that although most QTL for FER are minor QTL, some major QTL whose effects on FER were validated by near-isogenic lines could be managed by marker-assisted breeding [ 54 , 55 , 56 , 57 ]. In addition, as the number of mapping populations explored increased, the overlapping of QTL for FER found in different populations started to be more common [ 55 , 58 , 59 ].…”
Section: Mapping Of Qtl For Fer And/or Fumonisin Content In Bi-parmentioning
confidence: 99%
“…However, conventional breeding can be hampered by the complex genetic architecture of resistance to fumonisin accumulation that appears to be controlled by many quantitative trait loci (QTL) of small effect [1]. In an attempt to avoid this problem, authors have tried to find markers linked to genes involved in resistance to Fusarium ear rot (FER) and/or fumonisin contamination to use them in marker-assisted selection programs [6][7][8][9][10][11][12]. Many studies were focused on detecting QTL for resistance to FER; QTL were identified in all chromosomes, except in chromosome 9.…”
Section: Introductionmentioning
confidence: 99%
“…Giomi et al . 26 reported QTL for ear rot accounting for 5% to 11.9% of the phenotypic variation in a bi-parental population. Another bi-parental population reported FSR QTL explaining up to 12.6% 27 , and GWAS panels representing the maize core diversity and U.S.A. inbred lines reported R 2 between 3% to 12% 19–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to the disease is indeed a quantitative trait under polygenic control 23 . Previous studies reported a number of quantitative trait loci (QTL) associated with FER resistance and identified multiple loci with relatively small effect 17,19,2426 . At the seedling stage, the evaluation of genetic resistance to Fusarium seedling rot (FSR) may benefit from seed inoculation with F .…”
Section: Introductionmentioning
confidence: 99%